Pengaruh Aktivitas Usaha Imigran Timur Tengah Terhadap Kesejahteraan Ekonomi Masyarakat - Masropah, Imas; Safei, Agus Ahmad; Aziz, Ali (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2023)
This study relates to knowing the business activities of Middle Eastern immigrants to the economy of the North Tugu Village community, then to find out the business activities of Middle East Immigrants in Tugu Utara Village and the economic conditions of the people in Tugu Utara Village. This research is a quantitative research with experimental methods. Data analysis in this study using product moment research techniques. The results of the research carried out, the results of the study were strong enough between the business activities of Middle East Immigrants on the economic well-being of the people of Tugu Utara Village, Cisarua District, Bogor Regency, amounting to 0.579. The influence of activity on the economy of the Tugu Utara Village Community in Cisurua Bogor District is 33.5% and the rest are other factors. It can be concluded that the business activities of Middle East Immigrants are positive for the welfare of the people of Tugu Utara Village, Cisarua District, Bogor Regency.